The Imperative for Improved Global Economic Coordination - Stiglitz, Joseph E. (World Bank, 2012)
While global coordination is absolutely essential, success in achieving it may prove difficult because economic globalization has outpaced political globalization. If we are to succeed, we will have to manage coordination better than we have in the past.